Apple, tree : writers on their parents - Funderburg, Lise (University of Nebraska Press, 2019)
"Apple, Tree features a slate of compelling, original essays that eloquently consider a trait they've each inherited from a parent, exploring how it affects the lives they lead today, how it shifts their relationship, and how it changes their sense of self." --